2010
DOI: 10.1007/s11426-010-3175-0
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, fluorescence and resonance Rayleigh scattering spectra of hydrophobic hydrogen bonding of eosin Y/Triton X-100 nanoparticles and their analytical applications

Abstract: In a weak acidic medium (pH 2.4-2.8), eosin Y molecules (H 2 L) could replace water molecules to associate with Triton X-100 to form hydrophobic hydrogen bonding complexes. These complexes could further aggregate to form nanoparticles through the squeezing action of the water phase and Van Der Waals force, resulting in changes in the absorption spectrum and fluorescence quenching of EY as well as the significant enhancement of resonance Rayleigh scattering. This enables the sensitive determination of Triton X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…It was shown that the ionassociation complex was not a simple mixture of the reactant and the ion association reaction was happened. Moreover, comparing curve b with curve d, we observed that the absorption peaks in 1092 cm À1 and 1243 cm À1 belonging to the g O-H of phenolic hydroxyl in EY were disappeared, 29 and the characteristic absorption peak in 1214 cm À1 was observed which could be attributed to the g O-H of carboxyl in EY, 25 these demonstrate that the HNCD + bound with -O À to form a neutral ionassociation complex. 30 The structural characteristics such as shape and size of the reactants and product were observed by TEM.…”
Section: Formation Of the Ion-association Complex And Its Composition...mentioning
confidence: 77%
“…It was shown that the ionassociation complex was not a simple mixture of the reactant and the ion association reaction was happened. Moreover, comparing curve b with curve d, we observed that the absorption peaks in 1092 cm À1 and 1243 cm À1 belonging to the g O-H of phenolic hydroxyl in EY were disappeared, 29 and the characteristic absorption peak in 1214 cm À1 was observed which could be attributed to the g O-H of carboxyl in EY, 25 these demonstrate that the HNCD + bound with -O À to form a neutral ionassociation complex. 30 The structural characteristics such as shape and size of the reactants and product were observed by TEM.…”
Section: Formation Of the Ion-association Complex And Its Composition...mentioning
confidence: 77%
“…Therefore, it is concluded that this electroneutral ionassociation has strong hydrophobicity, and they get close via squeezing effect of aqueous phase and self-aggregate by van der Waals force. [44][45][46][47] The procedure is shown as follows: a Tolerance level was calculated using mg mL À1 .…”
Section: Formation Of Ion-association Chelate Nanoparticlesmentioning
confidence: 99%
“…This method showed its high potential for the determination of metal ions [31], non-metallic inorganic substances [32,33], surfactants [34], biomacromolecules [35], and pharmaceuticals [36]. The method is characterized by high sensitivity, convenience in performance and simplicity in apparatus (usually common spectrofluorophotometer).…”
Section: Introductionmentioning
confidence: 99%